Laporan akhir penyelidikan delay in police investigations : a study of the underlying causes / Lee Chong Fook, Mazlifah Mansoor and Che Audah Hassan - Lee, Chong Fook; Mansoor, Mazlifah; Hassan, Che Audah (2007)
This research is to study the proposed amendment to Section 120 of the Criminal Procedure Code. The proposed changes criminalized any police failure to report their investigations within a certain time frame to the Public Prosecutor. The purpose of this research is to find out the causes for delays and prolonged investigations by the police officers.